A Microeconometric Analysis of the Effects of Strikes on Wages - Lacroix, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
This paper examines the hypothesis of a positive relationships between strikes and the level of negotiated wage agreements.